Bacterial isolates and drug susceptibility patterns in infected lesions of cutaneous leishmaniasis patients at ALERT hospital, Addis Ababa, Ethiopia - Gizealew Ayalew; Asegedech Asmamaw; Mistire Wolde; Regasa Diriba; Biruk Zerfu (BMC Infectious Diseases)
Abstract Bacterial infections commonly complicate cutaneous leishmaniasis (CL), worsening the disease and delaying healing. Despite this, there is a gap in research concerning the characteristics of pathogenic microorganisms associated in CL patients. This study aims to identify bacterial isolates and drug susceptibility patterns in CL patients. A purposive cross-sectional study was conducted among CL patients attending the ALERT hospital from January 2021 to June 2021. Standardized questionnaires were used to collect socio-demographic and clinical data. Each patient’s lesion was aseptically sampled with two swabs. The swabs were aseptically inoculated onto blood agar plates (BAP) and Mac Conkey agar (MAC) and cultured following standard protocols. The isolates were identified by gram staining, colony morphology, and biochemical testing. Antimicrobial susceptibility patterns were done using the disk diffusion technique according to 2021 CLSI guidelines. SPSS version 20 was used to enter and analyze data. In this study 384 CL patients (66.9% male), aged 2–85 years were enrolled. 390 pathogenic bacteria were isolated from CL lesions, with 58.0% and 42.0% Gram-positive and Gram-negative bacteria, respectively. S aureus (41.5%), coagulase-negative Staphylococci (14.4%), Citrobacter spp. (10.8%), Klebsiella spp. (9.9%), and Proteus spp. (7.9%) were the most commonly identified bacteria. Over 80% of the isolates demonstrated multi-drug resistance to two or more antibiotics. S. aureus showed high resistance to penicillin (86.4%), methicillin (83.9%), and tetracycline (47.5%). These findings highlight the critical needs of microbial diagnostics and antibiotic susceptibility testing in CL patients due to the rising prevalence of drug-resistance, including the multi-drug resistant bacteria.